Dressing for success in the classroom - Balasundaram, Angelina Anne *; Lai, Kok Hoe * (Sunway College Kuala Lumpur, 2015)
“A picture paints a thousand words” is a very famous quote by Frederick R. Barnard which has sparked a great level of curiosity in the researchers (Robbins, 2004). When a teacher figure braces the classroom from the first day and henceforth, he or she has etched a thought process in the minds of the students which will leave a lasting mark on them. Many researchers have been primarily focused on teaching methodology and teaching content which are regarded as the heavy weights of the teaching profession and in the process have brushed aside the minute factors, namely the attire of teachers, which are also as equally impactful, though they contribute in a more subtle manner (Gorham, Cohen, & Morris, 1999).This is the crux of the researchers’ study in which the focus will be directed at investigating whether or not the overall attire of the teacher figure has a significant impact on the students capacity of assimilating knowledge. The study will also encompass the clothing items deemed acceptable in the classroom which will be validated by the students’ acceptance level. Therefore, the research questions for this study will be (a) Does the attire of the teacher have an impact on learning effectiveness? (b) Attire has the greatest impact on students from which of the three pre-university programmes? (c) Attire has a greater impact on which gender? (d) Which attire articles are deemed acceptable by the students to be used by the teacher figure? From the preliminary study it showed that the students were affected by the attire of their teacher figure in which the mean of the three elements all were 3.5 and above. The level it affected the student population showed variations across the three pre-university programmes and gender. However, the students were very open in terms of attire worn by teachers in that they accepted various forms of attire which included denim and leather and also bold prints and shiny accessories. This acceptance also showed demographic variations.